Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s00477-011-0554-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking on the levels of urinary biomarkers of aromatic hydrocarbons in oil refinery workers

Abstract: Occupational exposures to aromatic hydrocarbons may be overwhelmed by mainstream and secondary smoking exposures. The objective of this study was to evaluate the influence of occupational exposures and smoking on benzene and toluene urinary metabolites. The metabolites were measured in pre and post-work shift urine specimens in oil refinery workers by gas chromatography/ mass spectrometry techniques. Post-shift concentration differences between non-smokers and smokers were statistically significant (at p-value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…The differences between cresol and hippuric acid (both are toluene metabolites) may be attributed to the different excretion times. Cresol is excreted 1 h after exposure, while the highest hippuric acid concentration is typically observed four to six hours after exposure [40,41]. O-Cresol showed low values compared to the BEI value of 0.3 mg g −1 of creatinine, which are in agreement with the low levels of airborne toluene.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The differences between cresol and hippuric acid (both are toluene metabolites) may be attributed to the different excretion times. Cresol is excreted 1 h after exposure, while the highest hippuric acid concentration is typically observed four to six hours after exposure [40,41]. O-Cresol showed low values compared to the BEI value of 0.3 mg g −1 of creatinine, which are in agreement with the low levels of airborne toluene.…”
Section: Discussionsupporting
confidence: 67%
“…The validity of these markers has been demonstrated for levels in the air exceeding 10 mg m −3 , which is the case in this study. However, to achieve better exposure assessments, the selection of appropriate urinary metabolites must consider other parameters such as metabolism mechanisms, time of sample collection, and other confounding factors [22,27,[40][41][42][43]. For example, smoking cigarette behavior has been confirmed to be a strong confounding factor for the urinary excretion of benzene metabolites at low levels and must therefore also be taken into consideration and evaluated in urinary biomonitoring [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed a more significant correlation between benzene, xylene isomers, phenol, and MEK in breathing zone and their urinary metabolites in smokers than nonsmokers (P = 0.03, P = 0.041, P = 0.02, P = 0.039, and P = 0.042, respectively). Some other studies reported significant differences between smokers and nonsmokers exposed to benzene in ambient air (15,38). The distribution of pollutants from petrochemical factories into the ambient air mainly depends on the process activities.…”
Section: Discussionmentioning
confidence: 97%
“…In general, petrochemical industries including large-industrial are the high important of viewpoint occupational health and industrial safety. They are one of the sources of releasing VOCs in the atmosphere, due to production process, storage tanks, and wastewater of these industries (14)(15)(16). Biological monitoring of workers exposed to solvents are supplement environmental monitoring and could be used to evaluate the effects of workload, work habits, exposure to various routes, and in health risk assessment (17,18).…”
Section: Introductionmentioning
confidence: 99%